Adsorption studies of methylene blue using selected agro-wastes as low cost adsorbents / Tiong Khing Gueok - Tiong, Khing Gueok (2015)

(untitled)
Today, there are a lot of dyes available commercially. Effluent discharge from textile industries to neighbouring water bodies is currently causing significant health problem. Synthetic dyes used in textile industries, if not treated prior to its disposal can enter our water systems and cause pollution. The study was performed using different agro-wastes namely kenaf (FH 990), banana stem, and sugarcane bagasse to produce low cost industrial adsorbents. Adsorption method was applied in removing methylene blue (MB) dye from aqueous solution. The aims of this study are to investigate the adsorption capacity under optimal parameters and compare the cost effectiveness together with the calorific value of adsorbents before and after the treatment. The characteristics of wastewater effluent was examined and the characteristics of adsorbents were determined by using FTIR, FESEM and BET analysis. The experiments were conducted in single adsorbate system by batch technique to determine the optimum condition for higher adsorbency. The determination of optimum conditions was carried out in different pH (2 - 10), agitation time (5- 300 minutes), initial concentration (10 – 70 mg/L) and temperature (20 - 100 ºC). The adsorption isotherms of Langmuir and Freundlich were employed to examine the equilibrium adsorption data. Thermodynamic parameters such as ΔH°, ΔS° and ΔG° were also calculated. The optimal adsorption was achieved by banana stem with the adsorption capacity of 68.47 mg/L and maximum removal percentage of 97.82 % for initial methylene blue concentration of 70 mg/L. The adsorption of methylene blue can be well describes by Freundlich isotherm and the adsorption process was found to be exothermic and spontaneous for all the adsorbents. Thus, all results indicated that the selected agro-wastes could be employed as an effective new low cost adsorbent for the removal of textile dyes from aqueous solutions.